Food supplementation protects Magnificent frigatebird chicks against a fatal viral disease. Issue 3 (6th February 2019) - Sebastiano, Manrico; Eens, Marcel; Pineau, Kévin; Chastel, Olivier; Costantini, David
Abstract: Outbreaks of wildlife diseases are occurring at an unprecedented rate. In French Guiana, recurrent episodes of frigatebird chicks' mortality due to a viral disease that first appeared in 2005 have recently turned into massive mortality episodes (85–95%) of chicks. One of the suggested hypotheses behind the appearance of the disease is food limitation due to the recent decline of local shrimp fishery boats on which frigatebirds rely for opportunistic feeding. We therefore experimentally fish‐supplemented frigatebird chicks with and without clinical signs of the disease. Food supplementation protected all chicks from the appearance of clinical signs of the disease and increased survival perspectives of sick chicks. These results suggest that food shortage might decrease resistance of chicks to infectious diseases and that using a specifically tailored food supplementation regime could be a complimentary tool to protect frigatebirds and other endangered birds from disease outbreaks threatening them with extinction.